Situation Report: Czechoslovakia, 9 July 1975 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. CPCS CC Session on the Economy: Hula and Baryl Promoted The Party Schooling Program for 1975-1976 The Communist Doctrine in the Teaching Process Salgovic Elected Slovak National Council Chairman